2016
DOI: 10.1016/j.jtice.2016.03.050
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced PAHs adsorption using iron-modified coal-based activated carbon via microwave radiation

Abstract: You may download, copy and otherwise use the AAM for non-commercial purposes provided that your license is limited by the following restrictions:(1) You may use this AAM for non-commercial purposes only under the terms of the CC-BY-NC-ND license.(2) The integrity of the work and identification of the author, copyright owner, and publisher must be preserved in any copy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 53 publications
(26 citation statements)
references
References 32 publications
5
21
0
Order By: Relevance
“…With ever-increasing concerns on environmental pollutions and energy crisis, the feedstock of activated carbon bers has gradually turned from petroleum resources to biomass-based materials. 15,16 Biomass is a promising feedstock for the preparation of activated carbon bers because of its abundance, environmental friendliness, low cost and good renewability. In addition, using biomass as a feedstock also affords a facile route to tailor the pore structures of the activated carbon bers.…”
Section: Introductionmentioning
confidence: 99%
“…With ever-increasing concerns on environmental pollutions and energy crisis, the feedstock of activated carbon bers has gradually turned from petroleum resources to biomass-based materials. 15,16 Biomass is a promising feedstock for the preparation of activated carbon bers because of its abundance, environmental friendliness, low cost and good renewability. In addition, using biomass as a feedstock also affords a facile route to tailor the pore structures of the activated carbon bers.…”
Section: Introductionmentioning
confidence: 99%
“…20,23,24 Previous studies revealed that the same adsorbent would perform a higher adsorption capacity for PHE than NAP. Ge et al 34 found that the adsorption amount of PAHs on Fe-modied AC followed the same order, and Xiao et al 18 reported similar behavior during the adsorption of NAP, PHE, and pyrene over AC in solution.…”
Section: Adsorption Kineticsmentioning
confidence: 89%
“…Hence, this is indicating that PHE has signicantly higher adsorptive affinity with hydrophobic groups on the surface of WAC surface, as well as more intense p-p interaction between p-electrons of PHE and benzene rings of WAC surface. 18,34,35 In summary, the inherent physicochemical advantages between PHE and WAC endow it with more competitive regardless of the type of adsorption system. So, since WAC preferential adsorption towards to PHE, this can explained that the adsorptive difference of the two PAHs in combination with Q e and Q cal values, of which PHE did not signicantly change, while NAP declined in both components.…”
Section: Adsorption Kineticsmentioning
confidence: 99%
“…Wide scans were conducted from 0 to 1000 eV with a pass energy of 50 eV. 3 2.3.4 Elemental analysis. Elemental analysis of carbon, hydrogen, nitrogen, and sulfur of HC and HMAC samples were performed using a Vario EL cube analyzer.…”
Section: Characterization Methodsmentioning
confidence: 99%
“…2 Naphthalene can be transported long distances in water then enriched in soil and living organisms, and is difficult to be effectively degraded by biodegradation because of its chemical stability. 3 Compared with various physicochemical methods for pollutant removal, adsorption is an effective method for the removal of naphthalene owing to its capability for efficiently adsorbing different kinds of contaminants and simplicity of design. 4 Researchers have developed a series of adsorbents for the removal of pollutants in liquid phase at present, such as modied ligno-cellulosic, 5 dry waste biolms, 6 dried biomass, 7 calcined oyster shells, 8 wheat straw 9 and persea based-activated carbon.…”
Section: Introductionmentioning
confidence: 99%